Effect of Buspirone, Fluoxetine and 8-OH-DPAT on Striatal Expression of Bax, Caspase-3 and Bcl-2 Proteins in 6-Hydroxydopamine-Induced Hemi-Parkinsonian Rats - Hamdollah Sharifi; Alireza Nayebi; Safar Farajnia; Rasool Haddadi (Tabriz University of Medical Sciences, 2015)
Purpose: The exact pathogenesis of sporadic parkinson's disease (PD) is still unclear. Numerous evidences suggest involvement of apoptosis in the death of dopaminergic neurons. In this study we investigated the effect of sub-chronic administration of buspirone, fluoxetine and 8-hydroxy-2-[di-n-propylamino]tetralin (8-OH-DPAT) in 6-hydroxydopamine (6-OHDA)-lesioned rats and assayed striatal concentrations of apoptotic (Bax, Caspase3) and anti-apoptotic (Bcl-2) proteins. Methods: 6-OHDA (8μg/2μl/rat) was injected unilaterally into the central region of the substantia nigra pars copmacta (SNc) of male Wistar rats and then, after 21 days lesioned rats were treated with intraperitonel (i.p) 1 mg/kg injections of buspirone, fluoxetine and 8-OH-DPAT for 10 consecutive days. Striatum of rats was removed at tenth day of drugs administration and were analyzed by western blotting method to measure Bax, caspase3 and Bcl-2 expression. Results: The results showed that the expression of Bax and caspase3 proteins was increased three weeks after 6-OHDA injection while they were decreased significantly in parkinsonian rats which were treated by buspirone, fluoxetine and 8-OH-DPAT. Bcl-2 was decreased and increased in parkinsonian rats and parkinsonian rats treated with buspirone, fluoxetine and 8-OH-DPAT, respectively. Conclusion: Our study indicates that sub-chronic administration of serotonergic drugs such as buspirone, fluoxetine and 8-OH-DPAT restores striatal concentration of apoptotic and anti-apoptotic factors to the basal levels of normal non-lesioned rats. We suggest that these drugs can be used as a potential adjunctive therapy in PD through attenuating neuronal apoptotic process.